Overdenture on dental remaining in oncological patients: Case report - de CARVALHO, Victoria Garcia [UNESP]; Moreira Júnior, Cláudio [UNESP]; Santos, Lucio Murilo Dos [UNESP]; Paes Júnior, Tarcísio José de Arruda [UNESP] (Editora Cubo, 2020)
Head and neck cancer occupy the seventh place among the most common neoplasms in the world, with an annual incidence of approximately 640,000 new cases. Radiotherapy treatment has been highlighted, because there is greater tissue preservation, possibility of regression of the disease, decreased tumor volume, prevention of possible tumor recurrences and metastases, and even total cancer cure, but patients undergoing radiotherapy are at high risk of osteoradionecrosis if they perform surgical interventions in the region, such as dental implants and dental extraction, making prosthetic rehabilitation of partially edentulous patients after treating oral cancer something complex and often omitted; although it is a crucial factor in restoring oral function. Thus, the aim of the present study was to describe the planning, treatment and follow-up of a twelve-month prosthetic approach to rehabilitate the lower arch shape and function of a partially edentulous patient undergoing head and neck radiotherapy with a full denture mucus supported and tooth retained. After twelve months of follow-up, it was possible to evidence the functional and aesthetic clinical success, with preserved occlusal pattern, soft and bone tissue around and dental roots.
Overdenture sobre remanescente dental em paciente oncológico: Relato de caso
Keywords: Head and Neck Neoplasms; Oral Rehabilitation; Overdentures; Radiotherapy